Data Driven UI Colour Selection for Enhanced User Engagement - Sandy Setiawan; Titih Nursugiharti; Fitra Putri Oganda; Henry Zainarthur (Blockchain Frontier Technology, 2026)
This study highlights the importance of color selection in user interface (UI) design, as it can influence users’ perceptions, emotional responses, and levels of engagement. Many applications still rely on designers’ intuition without strong empirical evidence. The objective of this research is to develop a data-driven framework for UI color selection that can measurably enhance user engagement and satisfaction. The method involves collecting a large dataset of color schemes from various popular applications, followed by preprocessing steps such as normalization, clustering, and analysis of the relationships between colors and emotional responses. In addition, user interaction metrics and engagement data are analyzed to evaluate the impact of specific color combinations. The results show that certain color palettes consistently generate higher levels of engagement, with specific hues and contrast levels improving users’ attention and effectiveness in completing tasks. The analysis also identifies patterns that can serve as guidelines for designers in selecting colors that balance aesthetic appeal and functional performance. The conclusion of this study is that adopting a data-driven approach to UI color selection leads to a significant improvement in user engagement, while also providing practical guidance for designers and developers to optimize digital interface experiences.